Mixes of Policy Instruments for the Full Decarbonisation of Energy Systems: A Review - Fleance George Cocker (Energies)
Stand-alone carbon pricing is still predominantly advanced as the policy instrument of choice for abating greenhouse gas emissions, although it has enjoyed limited support in practice. Against this background, the current paper investigates whether combinations of climate policy measures constitute a promising avenue for reaching zero emissions in the power, transport, buildings, and industry sectors. Adopting a sectoral approach, we review the international literature on instrument mixes and consolidate previous findings according to four widely employed evaluation criteria, namely environmental effectiveness, economic efficiency, social equity, and political feasibility. The performance of mixes along these dimensions is critically assessed by studying the inter-relationships between decarbonisation levers, decarbonisation barriers, and policy instrument characteristics. Our analysis suggests that carefully designed combinations of measures may perform better than stand-alone instruments in many instances, although trade-offs between policy objectives are inevitable. We show evidence that desirable instrument mixes should be tailored to the characteristics of targeted agents and technologies, but argue that some level of carbon pricing typically offers high potential for synergies with complementary measures in all sectors. The study focuses on Switzerland for illustrative purposes, yet the policy implications are far-reaching and drawn from experiences across Europe and North America.